A Novel Circulating MiRNA-Based Signature for the Diagnosis and Prognosis Prediction of Early-Stage Cervical Cancer. (16th December 2020) - Qiu, Huajuan; Liang, Duoxian; Liu, Limin; Xiang, Qun; Yi, Zhijun; Ji, Yanqin
Background: MicroRNAs (miRNAs) have been shown to play a key role in regulating the progression of cervical cancer (CC). This study aimed to develop a circulating miRNA-based molecular signature for the diagnosis and prognosis prediction of early-stage CC. Methods: This study included 112 patients diagnosed with early-stage CC, 45 patients confirmed with cervical intraepithelial neoplasia (CIN) and 90 healthy subjects. Compared to the normal controls, the expression level of miR-21 was increased, while the levels of miR-125b and miR-370 were decreased in CC in both GSE30656 and The Cancer Genome Atlas (TCGA) cohort. The expression levels and diagnostic value of these candidate miRNAs were then validated through qRT-PCR. Their diagnostic and prognostic values for early-stage CC were further explored. Results: Compared to the patients with CIN and healthy subjects, serum miR-21 was increased, while serum miR-125b and serum miR-370 were reduced in early-stage CC. In addition, combining these molecules yielded good performance for differentiating early-stage CC from CIN or healthy subjects. Moreover, strong association was found between serum miR-21 and lymph node metastasis (LNM) as well as recurrence-free survival of early-stage CC. Similar observations were found for serum miR-125b and serum miR-370. Patients with simultaneously high serum miR-21 + low serum miR-125b + low serum miR-370 suffered a high risk of LNM and recurrence, while those with low serum miR-21 + high serum miR-125b + high serum miR-370 had little risk for LNM and recurrence. Conclusions: Combining serum miR-21, miR-125b and miR-370 as a miRNA-based signature is promising for the detection and prognosis prediction of early-stage CC.